Analisis Penggunaan Sistem Informasi Inaportnet Terhadap Kepuasan Pengguna dan Dampaknya Pada Kinerja Karyawan pada Perusahaan Pelayaran di Kota Batam - Reza Firnanda; Shinta Wahyu Hati (Politeknik Negeri Batam, 2021)
This research aims to identify the use of Inaportnet Information Systems on User Satisfaction and Its Impact on Employee Performance at Shipping Companies in Batam City. This study uses quantitative methods with Path analysis test. The research population is Inaportnet system users at shipping companies in Batam City. The sampling method used purposive sampling. Collecting data using a questionnaire. The results of the first study that system quality has a direct and significant effect on user satisfaction, information quality has a significant effect on user satisfaction, service quality has a significant effect on user satisfaction, system quality has a significant effect on employee performance, information quality has a significant and negative effect on employee performance, service quality have a significant effect on employee performance, system quality, information quality, and service quality have a significant effect on employee performance, system quality, information quality, and service quality simultaneously have a significant effect on user satisfaction, system quality, information quality, service quality, and user satisfaction simultaneously has a significant effect on employee performance.